Empowering Organisations to Gain From Uncertainty: a Conceptualisation of Antifragility Through Leveraging Organisational Routines in Uncertain Environments - Albert Munoz; Mathew Todres; Laura Rook (Australasian Accounting, Business and Finance Journal, 2021)
Economic shifts, disruptive innovations, and competitive rivalries continuously reshape the operating environment of organisations. Such uncertainty impacts organisations and raises significant challenges. While many organisations tend to respond to uncertainty by adopting loss minimisation strategies, others see uncertainty as an opportunity to achieve gains. The latter view is exemplified in Taleb’s (2012) concept of ‘antifragility’, a property of systems that gain when exposed to uncertainty. For organisations, the challenge lies in the identification and execution of fundamental artefacts to accomplish work to achieve antifragile outcomes. One such artefact is the organisational routine; repeatable, regular patterns of behaviour and actions that influence performance. This paper conceptualises the intersection between antifragility, uncertainty management, and organisational routines literatures to identify four routine archetypes that can guide actions that contribute to organisational antifragility. Theoretically, this paper identifies how these archetypes arise from the interplay between temporal action (as tendencies towards proactive or reactive action) and risk mitigation strategies (as preference towards redundancies or flexibilities). Developed insights bring forth a foundation for predictive models of performance, and guidance for organisations aiming to thrive, rather than just survive, in uncertain environments. This paper concludes with the identification of further research avenues.
Keywords: Antifragility; Organisational Routines; Redundancy; Flexibility